A local innate immune response against Trypanosoma cruzi in the human placenta: The epithelial turnover of the trophoblast. (October 2016) - Liempi, Ana; Castillo, Christian; Carrillo, Ileana; Muñoz, Lorena; Droguett, Daniel; Galanti, Norbel; Maya, Juan Diego; Kemmerling, Ulrike
Abstract: Congenital Chagas disease, caused by Trypanosoma cruzi, is partially responsible for the progressive globalization of Chagas disease despite of its low transmission rate. The probability of congenital transmission depends on complex interactions between the parasite, the maternal and fetus/newborn immune responses and placental factors, being the latter the least studied one. During transplacental transmission, the parasite must cross the placental barrier where the trophoblast, a continuous renewing epithelium, is the first tissue to have contact with the parasite. Importantly, the epithelial turnover is considered part of the innate immune system since pathogens, prior to cell invasion, must attach to the surface of cells. The trophoblast turnover involves cellular processes such as proliferation, differentiation and apoptotic cell death, all of them are induced by the parasite. In the present review, we analyze the current evidence about the trophoblast epithelial turnover as a local placental innate immune response. Highlights: Congenital transmission of T. cruzi depends on complex interactions between parasite, maternal/fetal and placental factors. T. cruzi induces trophoblast turnover. Trophoblast turnover is proposed as a local placental innate immune factor.